Media, Populism and Hate Speech - Çoban, Savaş; İnceoğlu, Yasemin Giritl (Global Populisms, 2025)
This book offers an interdisciplinary analysis of populism, authoritarianism, and hate speech, integrating theoretical debates with empirical case studies. It examines how populist movements can evolve into authoritarian regimes, exploring the manipulation of media and democratic institutions. The book includes global case studies, such as Turkey, Hungary, and Brazil, highlighting the role of media in spreading propaganda and hate speech. It also addresses the methodological challenges of studying these phenomena and emphasizes the need for multidisciplinary approaches. The book serves as a valuable resource for academics, policymakers, and activists confronting the rise of populism and authoritarianism.